Midcarpal Hemiarthroplasty for Wrist Arthritis: Rationale and Early Results - Vance, Michael C. (Thieme Medical Publishers, 2012)
Midcarpal hemiarthroplasty is a novel motion-preserving treatment for radiocarpal arthritis and is an alternative to current procedures that provide pain relief at the expense of wrist biomechanics and natural motion. It is indicated primarily in active patients with a well-preserved distal row and debilitating arthritic symptoms. By resurfacing the proximal carpal row, midcarpal arthroplasty relieves pain while preserving the midcarpal articulation and the anatomic center of wrist rotation. This technique has theoretical advantages when compared with current treatment options (i.e., arthrodesis and total wrist arthroplasty) since it provides coupled wrist motion, preserves radial length, is technically simple, and avoids the inherent risks of nonunion and distal component failure. The KinematX midcarpal hemiarthroplasty has an anatomic design and does not disrupt the integrity of the wrist ligaments. We have implanted this prosthesis in nine patients with promising early results. The indications for surgery were as follows: scapholunate advanced collapse wrist (three), posttraumatic osteoarthritis (three), inflammatory arthritis (two), and Keinböck disease (one). Prospective data has been collected and the results are preliminary given the infancy of the procedure. The mean follow-up was 30.9 weeks (range: 16 to 56 weeks). The mean Mayo wrist score increased from 31.9 preoperatively to 58.8 (p < 0.05) and the mean DASH score improved significantly from 47.8 preoperatively to 28.7 (p < 0.05). There was a trend toward increased motion but statistical significance was not reached. Two patients required manipulation for wrist stiffness. There was no evidence of prosthetic loosening or capitolunate narrowing. The procedure is simple (average surgical time was 49 minutes) and maintains coupled wrist motion through preservation of the midcarpal articulation. The preliminary data show that it appears safe but considerably longer follow-up is required before conclusions can be drawn as to its durability, reliability, and overall success. The level of evidence for this study is therapeutic level IV (case series).